Comparative study of lateral entry versus crossed entry pinning for paediatric supracondylar humerus fractures: a case series - Kulambi, Vijayakumar S.; Mulla, Mahammad A. M.; Gombi, Praful R. (International Journal of Research in Orthopaedics, 2024)
Closed reduction and percutaneous pin fixation techniques have been proposed as treatment strategies for displaced supracondylar humeral fractures (SCHFs) in children. Commonly lateral pinning and cross pinning techniques are utilised for fixation. However, controversy exists regarding the selection of the appropriate procedure. A prospective study with 24 cases of displaced fracture supracondylar humerus, treated by lateral pinning and cross pinning, was conducted between August 2022 and May 2024 at Department of Orthopaedics at J.J.M. Medical College, Davangere. Patients were treated with either the lateral entry pin alone or the cross pinning with a combination of lateral entry pin and medial entry pin. Age, gender, fractured side, duration of surgery, postoperative complications, surgical approach, direction of pin application (lateral or cross), and Modified Flynn grading system grade was noted for study outcome. No difference was found between lateral pinning and crossed pinning groups in terms of the grade of the modified Flynn grading system and complications like iatrogenic ulnar nerve damage, loss of reduction. Pin tract infection was seen in one patient.